Incorporating participatory action research in attention bias modification interventions for addictive disorders : perspectives - Zhang, Melvyn Wei Bin (2019)
Participatory action research was introduced in the 1960s and early 1970s, but it has only been more widely adopted in the recent years. Such methodologies have since been applied to several web & mobile-based interventions in psychiatry. To date no prior review has scoped the extent of the application of such methodologies for web & mobile-based interventions in psychiatry. In this article, a scoping literature review was performed, and seven articles have been identified. The most common methodologies are that of co-design workshops; and increasingly service users and participants are included in these workshops. There remains a lack of application of such methodologies for addiction research. Increasingly, attention and cognitive bias modification interventions are more commonplace, given that they have been found to be effective in modifying underlying biases amongst individuals with addictive disorders. Unfortunately, there remains to be inherent limitations with web and mobile versions of attention and cognitive bias modification interventions. Participatory design research methods could help address these limitations and future research involving the conceptualization of new attention or cognitive bias modification applications ought to consider the incorporation of these research methods.